Underpaid and overworked: The challenges of private schools’ teachers in Ado-Ekiti Metropolis, Nigeria - Ojo, Stephen Sunday; Ayesoro, Sunday Adesina; Peter, Deborah Ibechone (goodwood publishing, 2025)
Purpose: It is therefore necessary to evaluate the challenges that private school instructors encounter as a result of heavy workload and low salary. Research methodology: The research is a cross-sectional survey, descriptive in nature. A self-structured questionnaire was used to collect data from the selected sample using a multi-stage sampling technique. Simple frequency and percentages were employed to describe the data. Results: Pay and working conditions offered to private school teachers do not reflect their abilities. Teachers in private education experience accumulation by dispossession as a result of the privatization of educational systems and frequently lack long-term job security. The findings reveal that the workload is excessive compared to remuneration, with limited benefits and minimal professional growth opportunities. Conclusions: The study concludes that the disparity between teachers’ efforts and rewards contributes to dissatisfaction and instability in the private education sector. These conditions may undermine the quality of teaching and long-term sustainability of the profession. Limitations: The paper only describes the experiences of private school teachers and therefore could not ascertain the degree of relationship between challenges faced by private teachers in working under conditions of being underpaid and overworked. Contribution: The study will be useful in understanding factors underlying the working conditions of private school teachers. It contributes to knowledge in the fields of industrial relations, human resources management, and the education industry, offering valuable insights for policymakers and stakeholders to improve teacher welfare and retention.